2021
DOI: 10.1021/acs.energyfuels.0c03184
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Ring Index (ARI): A Characterization Factor for Nonpolar Hydrocarbons from Molecular Weight and Refractive Index

Abstract: Crude oils consist of tens of thousands of components belonging to various hydrocarbon families, including n-alkanes, cyclo-alkanes, and aromatics. Because the experimental determination of the composition and molecular structure of each component is an infeasible task, it is common to use characterization factors that describe the nature of the pseudo fractions based on their bulk thermophysical properties. In this work, a new characterization factor, called the aromatic ring index (ARI), is developed based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…where, n D20 = refractive index at 20 • C [26,27]. The methods discussed in this section describe the complex mixture, which is the VGO, in terms of average structural features of the molecules, that is, groups of carbon and/or hydrogen types, in contrast to the compound group.…”
Section: Determination Of Refractive Index Aromatic Carbon and Hydrogen Content By The Total Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…where, n D20 = refractive index at 20 • C [26,27]. The methods discussed in this section describe the complex mixture, which is the VGO, in terms of average structural features of the molecules, that is, groups of carbon and/or hydrogen types, in contrast to the compound group.…”
Section: Determination Of Refractive Index Aromatic Carbon and Hydrogen Content By The Total Methodsmentioning
confidence: 99%
“…The aromatic ring index developed by Abutiqiya et al [26,27] was confirmed to properly predict the actual aromatic ring numbers of individual hydrocarbons and fluid catalytic cracking slurry oils characterized by NMR.…”
mentioning
confidence: 86%
See 3 more Smart Citations